EFEKTIVITAS PENGENDALIAN HAMA ULAT KANTUNG (Metisa plana) PADA TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq) DENGAN SISTEM INJEKSI BATANG DI KEBUN TANJUNG GARBUS PT. PERKEBUNAN NUSANTARA II - Mardiana Wahyuni; Marshal Arifin Sinaga; Suprandi Restua S (Jurnal Agro Estate, 2017)
Bagworrn is one of leaf eater caterpillar in oil palm cultivation. They can attack oil palm from nursery stage to the mature stage. It is difficulty to control the baguworm because their body covered with bag. This research wa carried out in the afdeling VI Tanjung Gambus Estate PT.Perkebunan Nusantara II from Juli-Agustus 2017. Descreptive design with secondary data taken from the estate (data October 2016-March 2017). Control system has been used in Tanjung Gambus estate was by injection. The result of this research show that bagworm control by steam injection is effective. Bagworm (Metisa Plana) population decline with average mortality from 27.27 (heavy attack) to 5.44 (medium) with percentage 86.67 %.